Hubungan Self Efficacy dan Dukungan Sosial terhadap Stres Akademik pada Siswa - Alnetia Dwi Kamirsa Amria; Nurfarhanah Nurfarhanah; Zadrian Ardi; Puji Gusri Handayani (Bulletin of Counseling and Psychotherapy, 2026)
Academic stress is a common psychological problem among students that can arise from academic demands, such as the large number of assignments, demands to complete assignments on time, pressure to achieve good grades, and high academic expectations. This study aimed to examine the relationships of self-efficacy and social support with academic stress among students of MAN Insan Cendekia Padang Pariaman, Indonesia. This study employed a quantitative approach with a correlational design. The sample consisted of 140 Grade X and XI students selected using proportional random sampling. The sampling criteria included students in Grades X and XI who were officially enrolled at MAN Insan Cendekia Padang Pariaman during the 2025/2026 academic year. Data were collected using Likert-type scales measuring self-efficacy, social support, and academic stress and were analyzed using descriptive statistics and regression analysis. The results showed that self-efficacy was in the low category (M = 86.18; SD = 19.50), social support was in the low category (M = 71.84; SD = 17.30), and academic stress was in the high category (M = 131.74; SD = 28.90). Self-efficacy was negatively and significantly related to academic stress (R = 0.501; R² = 0.251; p < 0.001), indicating that self-efficacy explained 25.1% of the variance in academic stress. Social support was also negatively and significantly related to academic stress (R = 0.403; R² = 0.163; p < 0.001), explaining 16.3% of the variance. Furthermore, self-efficacy and social support simultaneously showed a significant relationship with academic stress (R = 0.559; R² = 0.313; F = 56.637; p < 0.001). These findings indicate that higher self-efficacy and social support are associated with lower academic stress. The findings provide empirical support for the development of guidance and counseling services aimed at strengthening students' self-efficacy and social support to help them manage academic demands more adaptively.